Effect of stirrup ratio on impact response of BFRP-reinforced concrete beams under different energy levels. (March 2023) - Li, Jian; Zhang, Renbo; Jin, Liu; Lan, Dongqiu; Zheng, Min; Du, Xiuli
Highlights: The effect of stirrup ratio on the impact resistance BFRP RC beams was presented. Numerical simulations are conducted under 8 different impact energy levels. Nominal equal-damage analysis is performed based on energy dissipation. A simplified prediction method of BFRP RC beams is suggested and verified. Abstract: Fiber-reinforced-polymer (FRP) reinforced concrete structures are gradually applied in building, bridge, dam engineering, etc. Compared with the extensively-studied static mechanical properties, the research on the impact resistance of FRP-reinforced concrete beams is minimal. This study established and validated the 3D modeling approach of Basalt FRP (BFRP) reinforced concrete beams with different stirrup ratios. Numerical simulations were performed under different impact energy. The effects of the stirrup ratio and impact energy on the mechanical response of concrete beams were presented and analyzed. It can be concluded that the increasing stirrup ratio can restrict the development of bending-shear cracks and thus preclude shear plug failure. Under the given impact energy, as the stirrup ratio increases, the midspan peak and residual displacement are reduced. More stirrups are activated while stirrup peak strains decrease in the shear region. The increasing stirrup ratio enhances the integrity and overall rigidity of the beams, which is more effective at higher velocities. Moreover, a nominal equal-damage analysis on the beams was performed according to energy dissipation, which provides a reference for in-depth research and design. Finally, considering the relationship between the static load-carrying capacity and dynamic input energy of the beam, a semi-empirical simplified method for predicting the peak impact deflection of concrete beams was suggested and initially verified. The simplified prediction method provides new insights for impact mechanical response investigation and engineering structure design for BFRP-reinforced concrete beams.